Poland Syndrome: Its Prevalence and Associated Implications - Singh, Rajani; Gupta, Kavita (Current Overview on Disease and Health Research Vol. 3, 2022)
Literature search revealed that Poland syndrome is a musculoskeletal birth defect with variable appearance. Classically, it presents as partial or full absence of pectoral muscles, breast along with upper limb anomalies. Limb anomalies may range from syndactyly to phocomelia. The Poland syndrome is found to be scattered in population but familial cases with intrafamilial occurrence have also been observed. As regards etiopathogenesis is concerned many theories have been put forth but vascular disruption theory is the most accepted one. In addition to classical presentation, the Poland syndrome may occur in concurrent with syndactyly, phocomelia, defective rib and severe thoracic wall defects causing impaired lung function. At birth and during childhood symptoms may be mild and does not require surgical intervention. Surgery should be considered only in cases where symptoms are severe as in case of massive chest anomalies impairing pulmonary functions. Aim of the chapter is to consolidate the data relating to etiopathogenesis, clinical presentations and requirement of treatment in cases of Poland syndrome.